2016
DOI: 10.17860/mersinefd.282387
|View full text |Cite
|
Sign up to set email alerts
|

Eğitim Fakültelerindeki Öğretim Elemanlarının Hayat Boyu Öğrenme Yeterlikleri İle Hayat Çapında Öğrenme Alışkanlıklarının İncelenmesi

Abstract: Öz: Bilgide meydana gelen hızlı değişimler ve buna bağlı olarak yaşanan toplumsal gelişmeler, bireylerin bilgiye ulaşmalarında ve yeni öğrenmelere duyulan gereksinmelerinde yenilikleri de beraberinde getirmektedir. Bu süreç ile içinde bulunduğumuz bilgi çağında bireylerin her yaşta, her yerde ve her konuda öğrenmelerini destekleyen hayat boyu öğrenme kavramının önemi vurgulanmaktadır. Hayat çapında öğrenme kavramı ise zamana ve fiziksel ortamlara sığdırılamayan sınırsız bir öğrenme anlayışını ifade etmektedir.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
1
2
0
1
Order By: Relevance
“…In the literature review, it has been found that there are few studies on lifelong learning about academics and that there is no demographic information about the fields of science in which academics work. Similar to the results of the research, Ayçiçek and Yanpar Yelken (2016) found that the lifelong learning competencies of academics working in the field of educational sciences were found to be at a high level within the scope of the study conducted to examine the lifelong learning competencies of academicians working in the faculty of education. The reason why academicians working in the fields of health sciences, educational sciences, fine arts and philology have higher lifelong learning tendencies than academics working in the fields of engineering, agriculture, forestry and fisheries, science and mathematics, theology and architecture, planning and design.…”
Section: Lifelong Learning Tendency and Thinking Style Levels Of Acad...supporting
confidence: 80%
See 1 more Smart Citation
“…In the literature review, it has been found that there are few studies on lifelong learning about academics and that there is no demographic information about the fields of science in which academics work. Similar to the results of the research, Ayçiçek and Yanpar Yelken (2016) found that the lifelong learning competencies of academics working in the field of educational sciences were found to be at a high level within the scope of the study conducted to examine the lifelong learning competencies of academicians working in the faculty of education. The reason why academicians working in the fields of health sciences, educational sciences, fine arts and philology have higher lifelong learning tendencies than academics working in the fields of engineering, agriculture, forestry and fisheries, science and mathematics, theology and architecture, planning and design.…”
Section: Lifelong Learning Tendency and Thinking Style Levels Of Acad...supporting
confidence: 80%
“…It has also been found that there are studies in the literature that do not differ by researchers. Yavuz Konokman and Yanpar Yelken (2014) examined the perceptions of instructors on lifelong learning competencies; Ayçiçek and Yanpar Yelken (2016), on the other hand, did not find a significant difference between the academic titles of academicians and their lifelong learning levels in their study in which they examined the lifelong learning competencies and lifelong learning habits of the instructors.…”
Section: Lifelong Learning Tendency and Thinking Style Levels Of Acad...mentioning
confidence: 99%
“… HBÖ uygulamaları ve ilköğretim programlarının, yükseköğretim programlarının incelenmesi (Budak, 2009;Burai & Bušljeta Kardum, 2022;Yalkın & Işık, 2019;Yılmaz & Salman, 2022),  Anahtar yetkinlikler ve HBÖ uygulamaları (Bilasa & Taşpınar, 2017;Şahin vd., 2010),  HBÖ kuramsal ve kavramsal değerlendirme çalışmaları (Aksoy, 2013;Güleç vd., 2012),  Öğretmen adayı, öğretmen, yönetici ve öğretim üyelerinin HBÖ yeterliliklerine yönelik görüşleri (Akçay, 2021;Asgari vd., 2019;Ayçiçek & Yanpar Yelken, 2016;Ayra & Kösterelioğlu, 2015;Doğan & Kavtelek, 2015a;Duymuş & Sulak, 2018;Erdener & Gül, 2017;Evin Gencel, 2013;Gökyer & Türkoğlu, 2018;Hoşgörür, 2016;Kabataş & Karaoğlan Yılmaz, 2018;Karakuş, 2013;Kazu & Erten, 2016;Kozikoğlu, 2014;Küpana & Sazak, 2019;Özçiftçi & Çakır, 2015;Özgür, 2016;Şahin & Arcagök, 2014;Uçar & Uysal, 2019;Yıldız Durak & Tekin, 2020;Yılmaz, 2016),  Türkiye ve AB sürecine yönelik HBÖ yeterlilikleri incelemesi (Poyraz & Titrek, 2013;Terzioğlu Barış, 2013),  HBÖ'ye yönelik ölçek geliştirme çalışmaları (Doğan & Kavtelek, 2015b;Doğan & Çalışkan Toyoğlu, 2019b),  Kodlama eğitimi ve HBÖ yeterlilikleri ilişkisine yönelik çalışmalar (Yıldız Durak & Şahin, 2018),  Yetişkin eğitimi uygulamaları ve anahtar yeterliliklere yönelik çalışmalar (Babanlı & Akçay, 2018),  Okullarda HBÖ uygulamaları ve durum çalışmaları…”
Section: Introductionunclassified
“…Similar studies on the subject show the results that do not coincide with this finding and are parallel to the present findings. Tunca et al (2015) and Dundar (2016), university students, Yilmaz (2016) and Ayaz and Unal (2016) with teachers and instructors of Ayçiçek (2016) and Hojat et al (2003) 's work with doctors in life It was determined that the lifelearning tendencies of the students did not differ according to gender.…”
mentioning
confidence: 99%